2013
DOI: 10.2147/ijn.s43263
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy for human hepatic carcinoma cells using folate-functionalized polymeric micelles loaded with superparamagnetic iron oxide and sorafenib in vitro

Abstract: Background:The purpose of this study was to evaluate the inhibitory effect of targeted folatefunctionalized micelles containing superparamagnetic iron oxide nanoparticles (SPIONs) and sorafenib on human hepatic carcinoma (HepG2) cells in vitro, and to observe the feasibility of surveillance of this targeting therapeutic effect by magnetic resonance imaging. Methods: Sorafenib and SPIONs were loaded into polymeric micelles. The targeted nanocarrier was synthesized by functionalizing the micelles with folate. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 25 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…Further, targeted nanospheres have also been proved to be effective drug delivery carriers. Similar to previous studies, 37,38 we also entrapped nanosized signal revealed that AsPC-1 was a high EGFR-expressing cell line, whereas MIA PaCa-2 belongs to a weak expressing cell line. This corresponded well with confirmatory western blot results.…”
Section: Discussionsupporting
confidence: 85%
“…Further, targeted nanospheres have also been proved to be effective drug delivery carriers. Similar to previous studies, 37,38 we also entrapped nanosized signal revealed that AsPC-1 was a high EGFR-expressing cell line, whereas MIA PaCa-2 belongs to a weak expressing cell line. This corresponded well with confirmatory western blot results.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, the presence of a hydrophilic shell avoids hydrophobic-hydrophobic interactions that provoke SPIONs aggregation, so nullifying all advantages related to the nanomeric dimensions of the starting carrier [16]. Many natural and synthetic polymers such as poly(hydroxyethyl) aspartamide derivative [17] and [18], chitosan, ethyl cellulose, poly(lactide) acid, poly(lactide-co-glycolide) acid and poly(ethylene)glycol have been employed as coating agents for enhancing SPIONs stability and conferring surface functional groups available for further reactions [19] and [20]. However, some of these either are not sufficiently bioeliminable or degrade to acidic products often yielding to local inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these either are not sufficiently bioeliminable or degrade to acidic products often yielding to local inflammation. Therefore, new cost-effective polymers provided with excellent biocompatibility and versatility should be synthesized and studied in view of clinical applications [20], [21] and [22]. In this study we propose inulin-based copolymer as coating agent for SPIONs.…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid-conjugated MNPs are a classic example of targeted delivery using MNPs. Folic acid-conjugated MNPs were used to target human nasopharyngeal epidermal carcinoma [72], breast cancer [112] and human hepatic carcinoma [113]. Multifunctional MNPs were produced where coreā€“shell biodegradable magnetite nanospheres were conjugated to doxorubicin through a carboxyl linkage and functionalized with iminodiacetic acid-modified folate to provide tumor-targeting capability [114].…”
Section: Surface Functionalizationmentioning
confidence: 99%